2019
DOI: 10.1002/pbc.27617
|View full text |Cite
|
Sign up to set email alerts
|

Content review of pediatric ethics consultations at a cancer center

Abstract: Background/objectives Ethical challenges in pediatric oncology arise at every stage of illness. However, there are sparse data on the content of and reason for ethics consultations in the field. We sought to evaluate the content and characteristics of ethics consultations in pediatric patients at a cancer center. Design/methods We retrospectively identified ethics consultations performed for patients diagnosed with cancer at ≤21 years of age who were treated in the Department of Pediatrics from 2007 to 2017. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Facilitated ethics discussions and clinical ethics support services can aid care teams to clarify complex ethical problems. 31 Winter et al 32 found paediatric ethics consultations as rare, but when requested, they most often concerned issues related to non-beneficial treatments. According to Leland et al, 33 many paediatric ethics consultations involve provider moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Facilitated ethics discussions and clinical ethics support services can aid care teams to clarify complex ethical problems. 31 Winter et al 32 found paediatric ethics consultations as rare, but when requested, they most often concerned issues related to non-beneficial treatments. According to Leland et al, 33 many paediatric ethics consultations involve provider moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent reviewers analyzed the content of each ethics consultation note using an established schema developed to standardize the ethics consultation process and outcomes. 4 The reviewers (D.N.F., L.B., Y.A.) assessed primary, secondary, and tertiary ethical issues on the basis of the narrative portion of the consultant's note.…”
Section: Data Collectionmentioning
confidence: 99%
“…Lo anterior se convierte en un desafío para los profesionales de la salud, quienes, no solo en la práctica, sino también en la investigación, han desatendido las necesidades del hermano sano y quienes, en el marco del hacer el bien y la justicia, deben propender a reivindicar los derechos de dicha población por considerarse también vulnerable y afectada por la situación de cáncer infantil [52]. Asimismo, en el marco de la bioética en salud, el llamado es a evitar las aproximaciones reduccionistas a los complejos problemas que enfrentan los sujetos y las comunidades de cuidado, por tanto, en el área del cáncer infantil debe considerarse la afectación sistémica de los actores implicados, entre ellos, los hermanos sanos [53].…”
Section: Discussionunclassified